Efeito de diferentes soluções ácidas no comportamento da luz de restaurações de cerâmica de dissilicato de lítio - Watanabe, Denis [UNESP] (Universidade Estadual Paulista (Unesp), 2016)
The maintenance of optical characteristics of ceramic materials is critical, since pH, and temperature alterations, in an environment such as the oral cavity, can degrade this material, leading to treatment failure. Purpose. The purpose of this study was to evaluate the color stability (ΔE), translucency parameter, and contrast ratio of the lithium disilicate ceramic exposed to commonly used potentially colorant solutions. Material and Methods. Fifty lithium disilicate samples were prepared, and divided into 5 groups, according to the immersion solution (artificial saliva, orange juice, Coca-Cola, coffee, and red wine). Immersions in the acidic beverages were alternated with immersion in artificial saliva, which was performed in a thermocycler. The control group was immersed in artificial saliva at 37ºC, throughout the immersion period. After 168 hours of immersion, color parameters were assessed by a spectrophotometer, and calculated by using the CIELAB system, on 2 backgrounds (black and white), and in 2 moments: before (T0) and after (Tf) thermocycling. Data were submitted to analysis of variance followed by the Tukey HSD test (α=.05). Results. Greater color change (ΔE) was observed after immersion in orange juice and cola. Regarding the translucency parameter and contrast ratio, the immersion in coffee resulted in greater opacity and lower translucency of the material. Conclusions. Alterations in color stability, translucency parameter, and contrast ratio of the lithium disilicate ceramic were observed, according to the acidic solutions tested. Clinical Implications. The results of this study suggest that the type of commonly used acidic beverage is an important factor influencing the optical behavior of lithium disilicate ceramics

A manutenção das características ópticas dos materiais cerâmicos é fundamental, visto que em um ambiente como a cavidade oral, alterações de pH e de temperatura podem degradar esse material, conduzindo ao insucesso do tratamento. O presente estudo teve o objetivo de avaliar a estabilidade de cor, a translucidez e o grau de contraste de cerâmica de dissilicato de lítio exposta a bebidas ácidas de uso comum, potencialmente corantes. Material e Métodos. Foram confeccionadas 50 amostras de cerâmica de dissilicato de lítio, divididas em 5 grupos de acordo com a solução de imersão (saliva artificial, refrigerante de cola, café, suco de laranja e vinho tinto). As imersões nas bebidas ácidas foram realizadas intercaladas com imersão em saliva artificial em uma termocicladora e o grupo controle foi imerso em saliva artificial a 37ºC durante todo o período de imersão. Foram realizados 10.080 ciclos de 1 minuto cada (168 horas). As leituras foram realizadas por espectrofotometria de reflexão ultravioleta visível e calculadas por meio do sistema CIELAB, em dois fundos (preto e branco) e em dois momentos: antes (T0) e após a termociclagem (Tf). Os dados obtidos foram submetidos à análise de variância (ANOVA) e o teste Tukey foi aplicado, com significância de 5%. Resultados. A imersão em suco de laranja e em refrigerante de cola foram responsáveis por maior alteração de cor (ΔE) do material. Já com relação ao grau de contraste e parâmetro de translucidez, a termociclagem com imersão em café resultou em maior opacidade e menor translucidez do material
Keywords: Cor; Cerâmica; Cerâmicas odontológicas; Fenômenos ópticos; Estética dentária; Color